IMPLEMENTATION OF ARTIFICIAL INTELLIGENCE IN INCREASING THE QUALITY OF LEARNING - Nugroho, Aris Dwi; Anwar, Kasful (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The focus of this paper is on the implementation of Artificial Intelligence or artificial intelligence in improving the quality of learning. Artificial Intelligence is a process of modeling human thinking and designing a machine so that it can behave like a human or another term called cognitive tasks, namely how machines can learn automatically from data and information that has been programmed. The digital and dynamic nature of Artificial Intelligence also offers opportunities for user engagement that cannot be found in often out-of-date documents or in fixed environments. Artificial Intelligence will collect data from learning activities that have been carried out by users, and then will provide alternative learning solutions that suit user needs. Artificial Intelligence has the potential to encourage and accelerate the discovery of new learning boundaries and the creation of innovative technologies in learning, this is expected to improve the quality of learning.